Preparation of Graphene-Polyaniline-Cellulose Double Network Hydrogels Using One Pot Method by Gamma Irradiation with Electrochemical Properties - Deni Swantomo; Kris Tri Basuki; Sigit Sigit; Yadi Yunus (Indonesian Journal of Chemistry, 2018)
In order to achieve high performance of electrochemical properties, numerous efforts have been devoted to the development of advanced multi-component hybrid double network hydrogel materials. In this research, the double network hydrogels were synthesized using one pot method by graft copolymerization of aniline onto graphene and cellulose using gamma irradiation as initiator. The formation of the double network hydrogels was confirmed by the Fourier Transform Infrared Spectroscopy (FTIR) study. X-ray Diffraction (XRD) analysis showed that the crystalline was increased through graft copolymerization graphene-aniline-cellulose double network. It was found that the crosslink density increased with increasing aniline volume and increasing radiation doses inversely with the swelling degree. Electrochemical measurements exhibited that increasing aniline volume and radiation doses increased specific capacitance and conductivity of the hydrogels. When compared with the pure graphene, the synthesized double network hydrogels exhibits remarkably enhanced specific capacitance of 9.774 F g-1 and conductivity i.e. 4.766 x 10-2 Scm-1 in 0.5 M HCl solution at aniline volume 8 mL and radiation dose 80 kGy. The improved electrochemical properties of the double network hydrogels represented an alternative promising candidate for the application as energy storage devices and offered a new facile method.